An application of the degree-hours method to estimate the residential heating energy requirement and fuel consumption in Istanbul - Durmayaz, Ahmet; Kadıoǧlu, Mikdat; Şen, Zekai (Elsevier BV, 2000)
Cold season heating energy requirements in buildings can be estimated with the degree-hours method based on human comfort levels and available meteorological temperature records for a given area. Such estimations are especially significant for cities where fossil fuel consumption must be eliminated in favor of clean energy alternatives to reduce air pollution. This paper considers the city of Istanbul in Turkey and presents a detailed account for practical energy requirements and fuel consumption calculations. © 2000 Elsevier Science Ltd. All rights reserved.